Phosphorylation of cell cycle and apoptosis regulatory protein-1 by stress activated protein kinase P38γ is a novel mechanism of apoptosis signaling by genotoxic chemotherapy - Venkatesh, Jaganathan; Muthu, Magesh; Singaravelu, Indulekha; Cheriyan, Vino T.; Sekhar, Sreeja C.; Acharige, Nuwan C. P. N.; Levi, Edi; Assad, Hadeel; Pflum, Mary Kay H.; Rishi, Arun K. (Frontiers in Oncology, 2024)
CARP-1, a perinuclear phospho-protein, regulates cell survival and apoptosis signaling induced by genotoxic drugs. However, kinase(s) phosphorylating CARP-1 and down-stream signal transduction events remain unclear. Here we find that CARP-1 Serine (S)626 and Threonine (T)627 substitution to Alanines (AA) inhibits genotoxic drug-induced apoptosis. CARP-1 T627 is followed by a Proline (P), and this TP motif is conserved in vertebrates. Based on these findings, we generated affinity-purified, anti-phospho-CARP-1 T627 rabbit polyclonal antibodies, and utilized them to elucidate chemotherapy-activated, CARP-1-dependent cell growth signaling mechanisms. Our kinase profiling studies revealed that MAPKs/SAPKs phosphorylated CARP-1 T627. We then UV cross-linked protein extracts from Adriamycin-treated HeLa cervical cancer cells with a CARP-1 (614–638) peptide, and conducted liquid chromatography-tandem mass spectrometry (LC-MS/MS) analyses of the peptide-bound protein complexes. This experiment revealed SAPK p38γ interaction with CARP-1 (614–638) peptide. Our studies further established that SAPK p38γ, but not other MAPKs, phosphorylates CARP-1 T627 in cancer cells treated with genotoxic drugs. Loss of p38γ abrogates CARP-1 T627 phosphorylation, and results in enhanced survival of breast cancer cells by genotoxic drugs. CARP-1 T627 phosphorylation was also noted in breast tumors from patients treated with radiation or endocrine therapies. We conclude that genotoxic drugs activate p38γ-dependent CARP-1 T627 phosphorylation to inhibit cell growth.